Temperature dependent development of Phenacoccus solenopsis under laboratory conditions - Kumar, Sanjeev; Kontodimas, Ch. (ENTOMOLOGIA HELLENICA, 2012)
Cotton mealybug, Phenacoccus solenopsis Tinsley (Hemiptera: Pseudococcidae) is an important cotton pest in Punjab, India. Development of the immature stages (four instars in female and five in male) of P. solenopsis was observed at nine constant temperatures (15, 18, 20, 25, 30, 34, 35, 38, 40°C). Using the linear model, the lower temperature threshold (tmin) for development was estimated to be 4.93 and 2.95°C and the thermal constant (K) was 333.33 and 454.54 degree days for female and male, respectively. In addition, three nonlinear models (Lactin, Bieri-1 and 3rd order polynomial) were tested to describe the relationship between temperature and development rate and to estimate the upper developmental threshold (tmax) and the optimum temperature for development (topt). Our results proved that the Bieri-1 and Lactin models and provided the best fit (r2 = 93,4 – 99,9%) and estimated accurately all the three critical temperatures, ranged tmin = 5.06 – 5.25°C, topt = 33.55 – 33.60°C, tmax = 39.99 – 40.00°C, for the total development of females and tmin = 2.82 – 3.16°C, topt = 34.01 – 34.04°C, tmax =40.00 – 40.10°C, for the total development of males.